The influence of different forms of apple products on all-cause mortality in patients with hypertension - Sun, Chuang; Chen, Yingying; Guan, Yue; Zeng, Yiming; Li, Jie; Chen, Liang (Frontiers in Nutrition, 2025)
ObjectiveApple consumption has a positive effect on human health. Some studies have shown that an appropriate amount of apple intake can reduce the incidence of hypertension. However, few studies have investigated whether eating different forms of apples has the same benefits as eating whole apples. This study is aimed to evaluate the effect of different forms of apple on all-cause mortality in patients with hypertension.MethodsThe study included 2,368 patients with hypertension. All participants were followed up for at least 10 years. Cox regression model was constructed to analyze the correlation between apple, apple juice, and apple sauce consumption and all-cause mortality in patients with hypertension.ResultsThe consumption of apples 3–6 times/week was associated with a 48% reduction in the risk of all-cause mortality in patients with hypertension (HR = 0.52, 95% CI: 0.37–0.72, p < 0.001). However, the consumption of apple juice (HR = 1.02, 95% CI: 0.67–1.56, p = 0.930) and sauce (HR = 1.28, 95% CI: 0.59–2.74, p = 0.531) tended to increase the risk of death in patients with hypertension, although this study did not obtain a statistically result.ConclusionModerate consumption of whole apples is associated with a reduced risk of all-cause death in patients with hypertension, whereas apple juice and sauce may increase the risk of death.